Public goods, private consumption, and human-capital formation: On the economics of volunteer labour supply - Eike Emrich; Christian Pierdzioch (Europäisches Institut für Sozioökonomie e. V., 2015)
Economists use three types of models to describe volunteer labour supply: the publicgoods model, the private-consumption model, and the human-capital model. We used data from an online survey questionnaire of volunteers working for the German Red Cross to study the extent to which each type helps to explain volunteer labour supply. To this end, we empirically studied various correlates of volunteer labour supply, including the components of utility that agents receive from volunteering. We used boosted regression trees to trace out the main correlates of volunteer labour supply, to study the relative contributions of the utility components, and potential interaction effects betwen the utility components and other correlates.
urn:nbn:de:bsz:291-scidok-68208; hdl:20.500.11880/23506
Keywords: 330; Volunteer labour supply; Boosted regression trees; German Red Cross; Ehrenamt; Deutsches Rotes Kreuz